Psychology as a Biological Science - Biswas-Diener, Robert; Diener, Ed (Open textbook library., 2020)
This textbook provides standard introduction to psychology course content with a specific emphasis on biological aspects of psychology. This includes more content related to neuroscience methods, the brain and the nervous system. This book can be modified: feel free to add or remove modules to better suit your specific needs. Please note that the publisher requires you to login to access and download the PDF.